The story of pocahontas and John Smith as a symbolic American folktale - Espinoza Roche, Ana; Ruilova Narváez, Diego
The Story of Pocahontas and John Smith as a Symbolic American Folktale, is a work that shows how Pocahontas became, through the years, an emblematic part of The United States culture. She has been known for years as a simple myth thanks to Hollywood, but we have tried to make her stand out as the key in the birth of a new and powerful nation: The United States of America. This work was not only focused on Pocahontas, but also on the early attempts to found colonies in The New World by the British. During the sixteenth century, the British made attempts to settle Virginia, which was finally unsuccessful. Another topic developed was about Jamestown, its beginning, its location, its difficulties, and its progress due to tobacco cultivation and commercialization. However, during the first years, the colony went through many crises and would not have survived if it would not have been for the assistance of Pocahontas, her people, and her friend Captain John Smith. We dedicated a chapter to John Smith, his life, his works, and his adventures in Europe, Asia, Africa, and America. He was one of the first American heroes and the first British writer in The New World. Moreover, he was not only an excellent explorer and soldier, but he was also a writer and a cartographer. Finally, Pocahontas had to be considered and remembered for establishing peaceful relations between two new cultures. Additionally, she had been represented as a romantic figure in American history.